PENERAPAN LAYANAN BIMBINGAN KELOMPOK DALAM MEMBENTUK KARAKTER SISWA KELAS XI DI SMAN 1 BAITUSSALAM ACEH BESAR - Nura Yudrika; Wanty Khaira (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2019)
Character is a character (behavior) or character (disposition)Â inherent in a person. In its formation, many character influenced by environmental factors, namely habits in SMAN 1 Baitussalam Aceh Besar many students who point to bad characters such as lack of respect for the teacher, indifference, ditching and smoking, this the consequences and lack of supervision of student habits. The purpose of this study is to find out whether the application of group guiding services can influence the formation of student character. This study uses quantitative techniques with an experimental approach using One Group Pre-test and Post-test Design. The population of this study is 41 students of social sciences class XI and the sample of this study is 5 students who are selected through the purposive side by categorizing students with low character levels. Data was collected through a Likert scale. Instrument analysis includes validity and reliability analysis. Data analysis using SPSS 20 and t-test. The results of this study is indicate a change in the value of student character scale with an average value of 664 post-test, compared with an average score of 574 pre-test. Based on paired sample test analysis, it is known that there are differences before and after the provision of group guidance services to the character of students in SMAN 1 Baitussalam Aceh Besar, with data t count> t table (13.059> 2.131) or Sig <0.00 so that Ha is accepted and Ho is rejected. This means that group guidance services provided as a treatment for changing student character have a positive effect.